A Comment on: "Patient and Tumour Characteristics of Keratoacanthoma in a Large, Community-based Cohort Study from Queensland, Australia" - Daniel Mazzoni; Jim Muir (Medical Journals Sweden, 2021)
Abstract is missing (Short communication)